Use of Pfeifer incision for treatment of unilateral incomplete cleft of lip - Rajeev Pandey (Wolters Kluwer Medknow Publications, 2017)
Cleft lip (CL) is commonly classified as complete or incomplete. In incomplete CL, there is a minimal distortion of orofacial region. Most of the times, it is treated with incisions which are used for complete CL. Here, we reported the use of Pfeifer incision for treatment of incomplete CL. The logic behind using this incision was that it does not involve noncleft tissue of lip in incomplete CL. Two patients were treated using this technique. Postoperatively following parameters were assessed: white roll match, vermilion match, and lip length postoperative scar and cupids bow form to determine the success of the technique. All the patients were successfully treated.